Exosome mediated biological functions within skeletal microenvironment - Wang, Zhikun; Zhao, Zhonghan; Gao, Bo; Zhang, Lingli (Frontiers in Bioengineering and Biotechnology, 2022)
Exosomes are membranous lipid vesicles fused with intracellular multicellular bodies that are released into the extracellular environment. They contain bioactive substances, including proteins, RNAs, lipids, and cytokine receptors. Exosomes in the skeletal microenvironment are derived from a variety of cells such as bone marrow mesenchymal stem cells (BMSCs), osteoblasts, osteoclasts, and osteocytes. Their biological function is key in paracrine or endocrine signaling. Exosomes play a role in bone remodeling by regulating cell proliferation and differentiation. Genetic engineering technology combined with exosome-based drug delivery can therapy bone metabolic diseases. In this review, we summarized how exosomes derived from different skeletal cells (i.e., BMSCs, osteoblasts, osteocytes, and osteoclasts) regulate the skeletal microenvironment through proteins, mRNAs, and non-coding RNAs. By exploring the role of exosomes in in the skeletal microenvironment, we provide a theoretical basis for the clinical treatment of bone-related metabolic diseases, which may lay the foundation to improve bone tumor microenvironments, alleviate drug resistance in patients.